Legal Certainty Aspects of the Implementation of Electronic Integrated Mortgage Rights Services at the National Land Agency of Majalengka District - Setiawan Budiman, Puja; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the implementation of electronically integrated mortgage services at the National Land Agency of Majalengka Regency and analyze the implementation of legal certainty against obstacles in the implementation of mortgage services at the National Land Agency of Majalengka Regency. The approach method in this study is a sociological juridical approach. The research specifications used are descriptive analytical research. The type of data uses primary and secondary data. The data analysis method used is the theory of legal effectiveness according to Soerjono Soekanto and the theory of legal certainty according to Gustav Radbruch. The results of the research and discussion in this study are: 1) The implementation of electronically integrated Mortgage Rights services at the National Land Agency of Majalengka Regency is a strategic aspect in order to increase efficiency, transparency and accountability of land services in accordance with the mandate of Law Number 4 of 1996 concerning mortgage rights on land Jo. Government Regulation Number 24 of 1997 concerning Land Registration, Jo. Regulation of the Head of the National Land Agency Number 1 of 2020 concerning the implementation of electronic mortgage rights services, the effectiveness of electronic mortgage rights registration is a key aspect in accelerating registration, submission and ratification of Mortgage Rights appropriately and transparently, minimizing manual interventions that cause deviations or corrupt practices and providing easy access to services to the public and business actors without having to be physically present at the land office. This is in line with the provisions of Law Number 25 of 2009 concerning Public Services which emphasizes the importance of fast, accurate, transparent and accountable services as part of good governance. 2) The implementation of Electronic Mortgage Rights (HT-el) in Majalengka Regency still faces various complex problems, especially the inconsistency between the Regulation of the Minister of ATR/BPN No. 9 of 2019 and Law No. 4 of 1996 concerning Mortgage Rights which gives rise to dualism of regulations and legal uncertainty, especially in terms of the form and validity of documents. In addition, the evidentiary power of electronic documents in the HT-el system is still questionable in the event of a dispute, especially if it is not equipped with an adequate security and authentication system. The obligation of Land Deed Officials (PPAT) to make a statement of document validity has also been highlighted because it is considered to burden legal responsibilities unilaterally. Another problem is the low readiness of facilities, infrastructure and human resources both at the Majalengka Regency Land Office and external users such as PPAT and banks which hinders the optimization of the implementation of HT-el as a whole in the Majalengka Regency area.